Clinical‐genetic features and peculiar muscle histopathology in infantile DNM1L‐related mitochondrial epileptic encephalopathy. Issue 5 (9th March 2019) - Verrigni, Daniela; Di Nottia, Michela; Ardissone, Anna; Baruffini, Enrico; Nasca, Alessia; Legati, Andrea; Bellacchio, Emanuele; Fagiolari, Gigliola; Martinelli, Diego; Fusco, Lucia; Battaglia, Domenica; Trani, Giulia; et al.
Abstract: Mitochondria are highly dynamic organelles, undergoing continuous fission and fusion. The DNM1L (dynamin‐1 like) gene encodes for the DRP1 protein, an evolutionary conserved member of the dynamin family, responsible for fission of mitochondria, and having a role in the division of peroxisomes, as well. DRP1 impairment is implicated in several neurological disorders and associated with either de novo dominant or compound heterozygous mutations. In five patients presenting with severe epileptic encephalopathy, we identified five de novo dominant DNM1L variants, the pathogenicity of which was validated in a yeast model. Fluorescence microscopy revealed abnormally elongated mitochondria and aberrant peroxisomes in mutant fibroblasts, indicating impaired fission of these organelles. Moreover, a very peculiar finding in our cohort of patients was the presence, in muscle biopsy, of core like areas with oxidative enzyme alterations, suggesting an abnormal distribution of mitochondria in the muscle tissue. Abstract : DNM1L de novo dominant variants impaired mitochondrial fission and produced the abnormal distribution of mitochondria in the muscle tissue.